Ensamblaje de un prototipo de humidificador de aire automatizado con implementación de un autómata programable - Pérez Llerena, Ruller David (2025)
The general objective of this thesis was: to assemble a prototype of an automated air humidifier with the implementation of a programmable automaton, consisting of: an evaporator, a programmable logic controller, a temperature controller integrated with a sensor, a relative humidity controller integrated with a sensor, an extractor and an electric heater. This objective was achieved by designing and simulating a control circuit, considering the following order of connections in the programmable logic controller: the temperature and relative humidity sensors, the electric heater and the extractor, are connected to the inputs I3 and I4 and to the physical outputs Q1 and Q2, respectively. He results indicated that: if the water temperature (Water) is lower than the set point (80 °C), the temperature sensor contact (I3) closes, turning on the electric heater (Q1), demonstrating that there is an inverse relationship between Q1 and Water. The evaporation rate of water changes in relation to temperature and time, from (0.000635 kg/s, 33.6 °C, 0 s) to (0.000669 kg/s, 81.8 °C, 780 s) and is constant (0.000666 kg/s) for values close to the set point (80 °C). If the relative humidity (Aire) is greater than the set point (95 %), the contact of the relative humidity sensor (I4) closes turning on the extractor (Q2), verifying that there is a direct relationship between Q2 and Aire. In this way, the general objective was met and at the same time the general hypothesis was tested.